TICK-BORNE VIRUSES OF WEST PAKISTAN: II. HAZARA VIRUS, A NEW AGENT ISOLATED FROM IXODES REDIKORZEVITICKS FROM THE KAGHAN VALLEY, W. PAKISTAN - BEGUM, FATIMA; WISSEMAN, C. L.; CASALS, J. (Oxford University Press, 1970)
Begum, F., C. L Wisseman, Jr. (Dept. Microbiology, School of Medicine, Univ. of Maryland, Baltimore, Md. 21201) and J. Casals. Tick-borne viruses of West Pakistan. II. Hazara virus , a new agent isolated from Ixodes redikorzevi ticks from the Kaghan Valley, W. Pakistan. Amer. J. Epid ., 1970, 92: 192–194.—A virus isolated from Ixodes redikorzevi ticks collected from the vole, Alticola roylei , in subarctic terrain at 12,000 ft. in the Kaghan Valley, Hazara District, of W. Pakistan has been shown to be a hitherto undescribed viral agent with the general properties of an arbovirus. It is serologically related to, but distinct from, another virus from the plains of West Pakistan which in turn has been found to be similar to, or identical with, Congo virus of Africa and subsequently the virus of Crimean hemorrhagic fever.